Hypokalemic periodic paralysis: an unusual presentation of primary hyperparathyroidism - S., Zahir Hussain; K., Rakesh Chandru (International Surgery Journal, 2018)
Primary hyperparathyroidism is an endocrine condition characterized by hyper secretion of parathyroid hormone (PTH). It has a wide varied clinical presentation from mild nonspecific symptoms to classical disease. We herein report two cases of primary hyperparathyroidism who were presented as hypokalemic periodic paralysis. The aim of this case report is to highlight this unusual presentation of primary hyperparathyroidism. Patients presenting with hypokalemic periodic paralysis should be evaluated for the possibility of primary hyperparathyroidism. Surgeons should be aware of this unusual presentation of primary hyperparathyroidism thereby it can be detected earlier, and prompt treatment can be offered before the disease progresses.